PERAN E-COMMERCE DALAM MENGEMBANGKAN USAHA SANDAL SPON DI DESA KARANGREJO KECAMATAN GEMPOL KABUPATEN PASURUAN - Azizah, Zahrotul; Fitrianah, Listin; Purnama, Agus Rachmad (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. Electronic Commerce (E-Commerce) is a marketing system using electronic media. E-commerce is an alternative choice for buyers during the pandemic because apart from being easy to use, buyers and sellers do not need to make direct contact. Aldiva Sponge Slippers UMKM located in Karangrejo Village, Gempol District, Pasuruan Regency is one of the UMKM that has not used E-Commerce. Partners have limitations in the marketing sector, namely they still do not have Human Resources (HR) in charge of marketing. Partners also do not have specific marketing media, especially online media, so sales are not maximized. The implementation of the service aims to overcome the problems faced by partners in details, namely the team developing e-commerce websites for partners, holding training on the operation of e-commerce websites, filling out e-commerce website content, and continuing with assistance. The implementation method used during the training was that the team invited all employees of the Aldiva Sponge Sandal SMEs and local village officials to take part in the training delivered by competent speakers in the field of digital marketing. The result of the activity is that the training participants benefit from the training held and are motivated to explore e-commerce. Partners already have new media for sales so that turnover increases. Abstrak. Electronic Commerce (E-Commerce) adalah sistem pemasaran menggunakan media elekronik. E-commerce menjadi alternatif pilihan pembeli di masa pandemi karena selain penggunaannya yang mudah, pembeli dan penjual tidak perlu melakukan kontak langsung. UMKM sandal spon Aldiva yang berlokasi di Desa Karangrejo Kecamatan Gempol Kabupaten Pasuruan merupakan salah satu UMKM yang belum menggunakan E-Commerce. Mitra memiliki keterbatasan pada sektor pemasaran yaitu masih belum memiliki Sumber Daya Manusia (SDM) yang bertugas di bidang pemasaran. Mitra juga belum memiliki media pemasaran yang spesifik khususnya media online sehingga penjualan belum maksimal. Pelaksanaan pengabdian bertujuan untuk mengatasi masalah yang dihadapi mitra dengan rincian yaitu tim membuatkan website e-commerce untuk mitra, mengadakan pelatihan tentang pengoperasian website e-commerce, melakukan pengisian konten website e-commerce, dan dilanjutkan dengan pendampingan. Metode pelaksanaan yang digunakan selama pelatihan adalah tim mengundang seluruh karyawan UMKM sandal Spon Aldiva dan perangkat desa setempat untuk mengikuti pelatihan yang disampaikan oleh pemateri yang kompeten dibidang pemasaran digital. Hasil dari kegiatan yaitu peserta pelatihan memperoleh manfaat dari pelatihan yang diadakan dan termotivasi mendalami e-commerce. Mitra sudah mempunyai media baru untuk penjualan sehingga omset meningkat.